Evaluation of analgesic and anti-inflammatory actions of indolealkylamines from toad venom in mice using lipidomics and molecular docking. (6th April 2021) - Xu, Dihui; Wang, Jiaojiao; Chen, Wuyue; Yang, Xinyi; Zhou, Jing; Ma, Hongyue; Di, Liuqing; Duan, Jinao
Abstract: Ethnopharmacological relevance: Toad venom is one of widely used traditional Chinese medicines due to its analgesic and anti-inflammatory activities. However, hydrophilic alkaloids from toad venom, which may have certain pharmacological activities, have not been systematic studied. Aim of the study: The aim of the study was to identify the indolealkylamines (IAAs) from toad venom and investigate the analgesic and anti-inflammatory actions. Materials and methods: The alkaloids were extracted and identified by high-resolution mass spectrometry. The analgesic abilities were determined using hot-plate test, formalin test and von Frey test. High-sensitivity lipidomics was used to investigate the regulatory function of IAAs on inflammatory eicosanoids. Besides, network pharmacology and molecular docking were used to demonstrate the candidate targets of IAAs. Results: 22 constituents have been characterized by high performance liquid chromatography (HPLC)-Triple TOF 5600, including six specific IAAs (serotonin, N-methyl serotonin, bufotenine, bufotenidine, bufothionine and dehydrobufotenine). Pharmacological studies showed that the IAAs from toad venom exerted significant analgesic activities at doses of 5, 15 and 45 mg/kg in vivo. Moreover, lipids analysis revealed IAAs might down-regulate inflammatory mediators from COX, LOX, DHA and LA pathways in formalin models, thus showing anti-inflammatory effect. The potent pharmacological function might because of the binding of IAAs and protein targets, such as sigma-1 receptor. Conclusion: The studies provided a systemic evidence for the analgesic and anti-inflammatory activities of IAAs from toad venom. It suggested that IAAs might be a potential candidate to reduce inflammatory pain disorders. Highlights: 22 characteristic components from toad venom water extraction were characterized by high-resolution mass spectrometer, including six specific indolealkylamines. The analgesic effect of indolealkylamines has been system evaluated in thermal, mechanical and chemical stimulation hyperalgesia models. Lipid profiling analysis provided evidences that the analgesic and anti-inflammatory actions of indolealkylamines were associated with down-regulation of lipdomics biomarkers. The analgesic and anti-inflammatory effects of indolealkylamines could be attributed to activating sigma-1 receptor with network pharmacology and molecular docking analysis.